Rest, Reactivity, and Recovery: A Psychophysiological Assessment of Borderline Personality Disorder - Eddie, David; Bates, Marsha E.; Vaschillo, Evgeny G.; Lehrer, Paul M.; Retkwa, Michelle; Miuccio, Michael (Frontiers in Psychiatry, 2018)
Difficulty regulating emotion is a cardinal feature of borderline personality disorder (BPD), yet little is known about the automatic psychophysiological processes involved in this phenotype. Inconsistent findings have emerged from studies that employed limited assessments (e.g., heart rate variability, skin conductance) of autonomic nervous system response to emotional contexts, and compared groups based on the presence or absence of BPD as a categorical diagnosis. This exploratory study assessed a comprehensive set of autonomic nervous system processes in 44 individuals (22 with BPD) at rest, in response to emotionally evocative stimuli, and during a subsequent recovery period. BPD was characterized with a dimensional measure of BPD symptom severity, as a well by categorical diagnosis. At baseline and across experimental tasks, higher heart rate was observed in those diagnosed with BPD compared to controls, and in those expressing greater BPD symptom severity. These effects, however, were fully mediated by differences in physical exercise. In contrast, during recovery from emotional activation, greater symptom severity predicted consistently higher levels of multiple sympathetic and parasympathetic processes compared to lower symptom severity. Overall, these findings suggest that the heart rate elevations sometimes observed in those diagnosed with BPD may be associated with individual and group differences in levels of physical exercise. Results further indicate that adaptive psychophysiological recovery responses following emotional challenge may be disrupted in proportion to BPD symptom severity, independently of exercise. Results highlight the utility of considering lifestyle factors and symptom severity in studies of emotional activation and regulation processes in BPD.